2010
DOI: 10.1007/s10773-010-0543-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Security of Controlled Quantum Secure Direct Communication by Using Four Particle Cluster States Against an Attack with Fake Entangled Particles

Abstract: A controlled quantum secure direct communication protocol (Zhang et al. Int. J. Theor. Phys. 48:2971-2976) by using four particle cluster states was proposed recently. The aim of Zhang et al. was that the successful realization of communication between Alice and Bob needed the cooperation of a controller, Charlie. However, we show that the controller Charlie's role could be excluded unknowingly. Using fake entangled particles and Bell measurement, the dishonest Bob who generates the initial signals can elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Using this attack, the control function of Charlie in the ZZZ protocol can be eliminated by the receiver Bob without the knowledge of Charlie. Moreover, this new attack is also valid for the improved scheme [Yang, Chai, Teng et al (2011)]. But to our disappointment, Qin did not give a further improvement.…”
Section: The New Improved Cqsdc Protocolmentioning
confidence: 91%
See 3 more Smart Citations
“…Using this attack, the control function of Charlie in the ZZZ protocol can be eliminated by the receiver Bob without the knowledge of Charlie. Moreover, this new attack is also valid for the improved scheme [Yang, Chai, Teng et al (2011)]. But to our disappointment, Qin did not give a further improvement.…”
Section: The New Improved Cqsdc Protocolmentioning
confidence: 91%
“…In fact, Bob wants to remove Charlie's control and obtain Alice's secret freely. Yang et al [Yang, Chai, Teng et al (2011)] presented a fake entangled particles attack on the ZZZ protocol, in which Bob prepares two Bell states rather than a four-qubit cluster state. Then, Bob can obtain Alice's secret information freely without Charlie's control.…”
Section: The New Improved Cqsdc Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…If it is secure against the participant attack, then it is also secure against the outside eavesdropping from Eve. Later studies showed that lots of quantum cryptographic protocols could not resist participant attacks [19][20][21][22][23][24][25][26][27].…”
Section: Security Analysismentioning
confidence: 99%